Coagulation Factor XII Levels and Intrinsic Thrombin Generation in Multiple Sclerosis - Ziliotto, Nicole; Baroni, Marcello; Straudi, Sofia; Manfredini, Fabio; Mari, Rosella; Menegatti, Erica; Voltan, Rebecca; Secchiero, Paola; Zamboni, Paolo; Basaglia, Nino; Marchetti, Giovanna; Bernardi, Francesco (Frontiers in Neurology, 2018)
Background: Factor XII (FXII) activation initiates the intrinsic (contact) coagulation pathway. It has been recently suggested that FXII could act as an autoimmunity mediator in multiple sclerosis (MS). FXII depositions nearby dentritic cells were detected in the CNS of MS patients and increased FXII activity has been reported in plasma of relapsing remitting and secondary progressive MS patients. FXII inhibition has been proposed to treat MS. Objective: To investigate in MS patients multiple FXII-related variables, including the circulating amount of protein, its pro-coagulant function, and their variation over time. To explore kinetic activation features of FXII in thrombin generation. Methods: In plasma from 74 MS patients and 49 healthy subjects (HS), FXII procoagulant activity (FXII:c) and FXII protein (FXII:Ag) levels were assessed. Their ratio (FXII:ratio) values were derived. Intrinsic thrombin generation (TG) was evaluated by different triggers. Results: Higher FXII:Ag levels (p=0.003) and lower FXII:ratio (p<0.001) were detected in MS patients compared with HS. FXII variables were highly correlated over four time points, which supports investigation of FXII contribution to disease phenotype and progression. A significant difference over time was detected for FXII:c (p=0.031). In patients selected for the lowest FXII:ratio, TG triggered by ellagic acid showed a trend in lower endogenous thrombin potential (ETP) in MS patients compared with HS (p=0.042). Intrinsic triggering of TG by nucleic acid addition produced longer time parameters in patients than in HS and substantially increased ETP in MS patients (p=0.004) and TG peak height in HS (p=0.008). Coherently, lower FXII:ratio, and longer lag time (p=0.02) and time to peak (p=0.007) point out a reduced response of FXII to activation in part of MS patients. Conclusions: In MS patients, factor-specific and modified global assays suggest the presence of increased FXII protein level and reduced function within the intrinsic coagulation pathway. These novel findings support further investigation by multiple approaches of FXII contribution to disease phenotype and progression.